Africa and the International Monetary Fund : papers presented at a symposium held in Nairobi, Kenya, May 13-15, 1985 - Helleiner, Gerald K.; International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1986)
Part 1 of this volume contains introductory overviews of the Fund and Africa. Part 2 contains the six papers, commissioned jointly by the Association of African Central Banks and the International Monetary Fund, and discussant's comments on them, as well as a paper prepared by Governor Ndegwa of Kenya on the economic crisis in Africa. Part 3 contains presentations made by seven panelists in a concluding session titled "Adjustment in Africa: What can Be Done?"
Includes bibliographical references.
rua 19/04/17
Loans
Keywords: International Monetary Fund; Africa